Five-Year Analysis of the Prevention of Colorectal Sporadic Adenomatous Polyps Trial - Arber, Nadir; Spicak, Julius; Rácz, István; Zavoral, Miroslav; Breazna, Aurora; Gerletti, Paola; Lechuga, Maria J; Collins, Neal; Rosenstein, Rebecca B; Eagle, Craig J; Levin, Bernard (The American journal of gastroenterology, 2011)
Subjects in the Prevention of Colorectal Sporadic Adenomatous Polyps (PreSAP) trial (PRESAP/NCT00141193/www.clinicaltrials.gov) were studied to determine efficacy and safety at a year 5 assessment. In this randomized, placebo-controlled, double-blind trial, 1,561 subjects with diagnosed colorectal adenomas removed within 3 months of the study's initiation were assessed after ~ 3 years on celecoxib followed by 2 years off. Studied in 107 primary and secondary care settings, subjects were stratified by cardioprotective aspirin use and randomized to receive orally 400 ng celecoxib (933 subjects) or placebo (628 subjects) once daily. Efficacy was measured by colonoscopy at years 1, 3, and 5, and safety was measured by investigators for the on-treatment period and collected by subject self-report over 2 years post-treatment. At year 5, the primary outcome measure was the rate of new adenomas measured cumulatively from baseline. This rate was statistically significantly lower in the celecoxib group (51.4%) than in the placebo group (57.5%; P<0.001). Similarly, the cumulative rate of new advanced adenomas was significantly lower in the celecoxib group (10.0%) than in the placebo group (13.8%; P=0.007). However, the year 5 interval measure, which was not cumulative and did not take the rates of previous years into account, showed that after 2 years off treatment, the celecoxib group (27.0%) was 1.66 times more likely to have new adenomas than the placebo group (16.3%; P<0.0001). Similarly, the percentage of patients with new advanced adenomas was significantly higher in the celecoxib group (5.0%) than in the placebo group (3.8%) (P=0.0072). The evaluation of safety from baseline through year 5 indicated that the risks of serious cardiac disorders (relative risk (RR) 1.66; 95% confidence interval (CI) 1.01-2.73), selected renal/hypertension events (RR 1.35; 95% CI 1.09-1.68), and general vascular (RR 1.34; 95% CI 1.08-1.68) and cardiac disorders (RR 1.59; 95% CI 1.12-2.26) were higher in those taking celecoxib than in those on placebo. The year 5 cumulative measures of the incidence of new and advanced adenomas were significantly lower in the celecoxib group than in the placebo group, but the year 5 interval rates of these measures were significantly lower in the placebo group than the celecoxib group, perhaps suggesting a release of cyclooxygenase-2 inhibition. Consistent with what has been previously reported, increased risk of renal/hypertension events and cardiac disorders associated with celecoxib therapy mandates caution in patient selection.